ALGORITHM OF FUNCTIONING OF A MACHINE-TRACTOR UNIT USING A FUEL MIXER SUPPLY SYSTEM - BURLAKA, SERHIY (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The switching scheme of operation of the machine-tractor unit with the use of the power supply system with the fuel mixer and the electronic control unit on the basis of Arduino Uno is presented. This scheme provides a fully adaptive power supply system for biofuels and their mixtures depending on the load-speed indicators and operating modes. The selection of circuit components is carried out. A linear algorithm for writing a control program for the engine power system has been developed, which ensures its energy efficiency and efficiency of the machine-tractor unit. During the operation of the machine-tractor unit there is a constant change of thermal, loading and speed modes. Internal combustion engines during operation usually operate in unstable modes - start, warm up, acceleration, braking, increase and decrease the load, stop. There is a need to develop a method of controlling the work processes of the diesel engine for its operation on a mixture of BF and PSU with electronic control of the fuel mixture depending on the operating modes. Engines are dynamically asymmetrical objects, ie the processes that take place when increasing and decreasing the load on the crankshaft, when starting and stopping the engine, differ from each other. The development of the algorithm for controlling the working processes of the diesel engine when working on a mixture of BF and PSU with electronic control of the fuel mixture depending on the operating modes of the engine will differ. Technical parameters of the diesel engine and power supply system that must be controlled during operation: torque, crankshaft speed, power, coolant temperature, PSU temperature, percentage of fuel mixture. Fuel consumption refers to economic indicators, to environmental - the composition and amount of harmful emissions. The value of these indicators directly depends on the modes of operation.